Peningkatan Kepatuhan Wajib Pajak Restoran dan Hotel melalui Pemeriksaan Wajib Pajak Daerah Kabupaten Badung: Improving Tax Compliance of Restaurant and Hotel Taxpayers through Local Taxpayer Audits in Badung Regency - Dewi, Kadek Arsita; Putri, Putu Indah Dianti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This non-profit initiative aims to increase tax awareness and compliance of restaurant and hotel taxpayers (WP) in the Badung Regional Government Area through a guided approach to local tax audits. Given the background of low taxpayer compliance and potential leakage of local revenue (PAD), this activity involved observations, interviews, and the implementation of more intensive and measured tax audits. Mentoring was provided to the staff of the Regional Revenue Agency (Bapenda) to improve their competence in conducting audits, as well as educating taxpayers about their tax obligations. The results of this activity showed a significant increase in taxpayer awareness and compliance, with more taxpayers registered and reporting their tax obligations, thereby contributing to the optimization of local tax revenue and supporting sustainable development in Badung Regency.